Journal of Population Research - Jatrana, Santosh; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
The Journal of Population Research is a peer-reviewed, international journal which publishes papers on demography and population-related issues. Coverage is not restricted geographically. The Journal publishes substantive empirical analyses, theoretical works, applied research and contributions to methodology. Submissions may take the form of original research papers, perspectives, review articles and shorter technical research notes. Special issues emanating from conferences and other meetings are also considered.
Keywords: Sociology; Demography; Demography; Sociology, general